Antimicrobial efficacy of the use of mouthwash with cetylpiridinium chloride for aerosol producing procedures : a systematic review = Eficacia antimicrobiana del uso del enjuague bucal concloruro de cetilpiridinio en procedimientos que generan aerosoles : revisión sistemática - Arce Toribio, Jackeline Paola; Arbildo Vega, Heber Isac; López Flores, Ana Isabel (2023)
The present research aims to determine the antimicrobial efficacy of the mouthwashes based on cetylpyridinium chloride (CPC), before aerosol producing dental procedures. A data search was performed during August 2021 in five databases MEDLINE (PubMed), SCOPUS, SCIELO, Cochrane Central Register of Controlled Trials (CENTRAL) and Google Scholar. Randomized clinical trials (RCTs) were included based on the PICO question, comparing the efficacy of the mouthwashes based on cetylpyridinium chloride (CPC), versus other mouthwashes and water, before aerosol producing dental procedures, papers in English, Spanish and Portuguese were included without time limits. The risk of the included studies was evaluated with the tool RoB 2.0. Number of registration PROSPERO N° CRD42021275982. 120 papers were obtained in the preliminary search, discarding those that didn't comply with the selection criteria, leaving only 3 studies. These papers reported the use of cetylpyridinium chloride (CPC) was effective for the reduction of bacteria during the ultrasonic prophylactic procedure. The use of CPC mouthwashes previous to the dental treatment with ultrasonic prophylaxis showed only antibacterial capacity.
El presente trabajo de investigación tiene como objetivo determinar la eficacia antimicrobiana de los colutorios a base de cloruro de Cetilpiridinio (CPC), previo a tratamientos dentales que generen aerosol. Se realizó una búsqueda bibliográfica hasta agosto del 2021 en cinco bases de datos: MEDLINE (vía PubMed), SCOPUS, SCIELO, Cochrane Central Register of Controlled Trials (CENTRAL) y Google Scholar. Se incluyeron ensayos clínicos aleatorizados (ECAs), basándose en la pregunta PICOS, que compare la eficacia del colutorio a base de cloruro de Cetilpiridinio (CPC) con otro colutorio, placebo o agua, previo a un tratamiento dental que genere aerosol, en los idiomas español, inglés o portugués y sin límite de tiempo. El riesgo de los estudios incluidos se evaluó con la herramienta RoB 2.0. Número de registro PROSPERO N° CRD42021275982. Se obtuvo un total de 120 artículos en la búsqueda preliminar, descartando aquellos que no cumplían con los criterios de selección, quedando sólo 3 articulos. Estos artículos informaron que el uso de CPC es efectivo para la reducción de bacterias durante el procedimiento de profilaxis con ultrasonido. El uso de los enjuagues bucales a base de CPC previo al tratamiento dental de profilaxis con ultrasonido sólo tiene eficacia antibacteriana.
En revista Odóvtos, vol. 25, no.3 (septiembre-diciembre 2023)
Descripción basada en el contenido visto el 16 de enero, 2025
También disponible en formato HTML y EPUB